Comparative Perspective on Curriculum Design: The Philippines and Global Educational Systems - Merianne D. Gucor; Mauricio S. Adlaon (Acta Pedagogia Asiana, 2026)
Curriculum design shapes national education systems and prepares learners to address global challenges. The Philippine K–12 curriculum, implemented in 2013, aligns with international standards but faces constraints related to flexibility, teacher autonomy, and interdisciplinary learning. This study systematically reviewed and compared Philippine curriculum frameworks with those of Finland, Singapore, the United States, and Japan to identify shared principles, distinctive features, and best practices. Peer-reviewed journal articles, national curriculum documents, and international education reports published between 2000 and 2025 were analyzed through thematic synthesis and comparative evaluation. The findings show that Philippine and global curricula share standards-based, competency-driven frameworks that emphasize 21st-century skills; however, they differ in governance, flexibility, teacher autonomy, and the integration of interdisciplinary learning. While the Philippines excels in contextualization and localization, other systems demonstrate greater adaptability, phenomenon-based learning, and technology-supported instruction. A re-conceptualized curriculum model is proposed that integrates global best practices while preserving local relevance. These insights highlight opportunities to enhance flexibility, empower teachers, promote interdisciplinary approaches, and integrate digital tools, thereby supporting evidence-based reforms and future research toward a globally aligned Philippine education system.